Dendritic Cells in Human Atherosclerosis: From Circulation to Atherosclerotic Plaques - Emily A. Van Vré; Ilse Van Brussel; Johan M. Bosmans; Christiaan J. Vrints; Hidde Bult (Hindawi Limited, 2011)
Background. Atherosclerosis is a chronic inflammatory disease with atherosclerotic plaques containing inflammatory infiltrates predominantly consisting of monocytes/macrophages and activated T cells. More recent is the implication of dendritic cells (DCs) in the disease. Since DCs were demonstrated in human arteries in 1995, numerous studies in humans suggest a role for these professional antigen-presenting cells in atherosclerosis. Aim. This paper focuses on the observations made in blood and arteries of patients with atherosclerosis. In principal, flow cytometric analyses show that circulating myeloid (m) and plasmacytoid (p) DCs are diminished in coronary artery disease, while immunohistochemical studies describe increased intimal DC counts with evolving plaque stages. Moreover, mDCs and pDCs appear to behave differently in atherosclerosis. Yet, the origin of plaque DCs and their relationship with blood DCs are unknown. Therefore, several explanations for the observed changes are postulated. In addition, the technical challenges and discrepancies in the research field are discussed. Future. Future studies in humans, in combination with experimental animal studies will unravel mechanisms leading to altered blood and plaque DCs in atherosclerosis. As DCs are crucial for inducing but also dampening immune responses, understanding their life cycle, trafficking and function in atherosclerosis will determine potential use of DCs in antiatherogenic therapies.